2012
DOI: 10.1371/journal.pone.0041069
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Characteristics and Underlying Risk Factors for Mortality during the Autumn 2009 Pandemic Wave in Mexico

Abstract: BackgroundElucidating the role of the underlying risk factors for severe outcomes of the 2009 A/H1N1 influenza pandemic could be crucial to define priority risk groups in resource-limited settings in future pandemics.MethodsWe use individual-level clinical data on a large series of ARI (acute respiratory infection) hospitalizations from a prospective surveillance system of the Mexican Social Security medical system to analyze clinical features at presentation, admission delays, selected comorbidities and recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 68 publications
3
18
1
1
Order By: Relevance
“…In line with previous studies [1619], immunosuppression (OR = 4.5 (95% CI: 2.1, 9.7)) was a significant risk factor of mortality among A/H1N1 inpatients in an adjusted multivariate logistic regression analysis. Similarly, chronic lung disease (OR = 3.5) and cancer within the last 12 months (OR = 4.3) were associated with an increase risk of death among A/H1N1 inpatients, which is also in agreement with previous studies [15, 17, 20].…”
Section: Discussionsupporting
confidence: 90%
“…In line with previous studies [1619], immunosuppression (OR = 4.5 (95% CI: 2.1, 9.7)) was a significant risk factor of mortality among A/H1N1 inpatients in an adjusted multivariate logistic regression analysis. Similarly, chronic lung disease (OR = 3.5) and cancer within the last 12 months (OR = 4.3) were associated with an increase risk of death among A/H1N1 inpatients, which is also in agreement with previous studies [15, 17, 20].…”
Section: Discussionsupporting
confidence: 90%
“…1 shows the temporal distribution of severely ill patients with laboratory confirmed influenza A(H1N1)pdm09 infection admitted to hospitals and the average daily number of attendances for ARI at government primary care clinics from epidemiological week (Eweek) 23 (7)(8)(9)(10)(11)(12)(13) in 2009 to E-week 32 (6)(7)(8)(9)(10)(11)(12) in 2010. In 2009, a steady increase in attendances for ARI was observed from E-week 25 (21)(22)(23)(24)(25)(26)(27) onwards, which peaked in E-week 30 (26 July-1 August), and decreased over the subsequent weeks until E-week 36 (6)(7)(8)(9)(10)(11)(12).…”
Section: Definition Of Time Periodsmentioning
confidence: 99%
“…Temperate countries such as Germany, Greece, Spain, England, Canada and Mexico, observed a second wave of patients with influenza A(H1N1)pdm09 infection during their post-pandemic period or post-pandemic influenza season [10][11][12][13][14][20][21][22]. A study conducted in England reported a greater burden of severe illness with more deaths, more critical care admissions and more hospital admissions due to influenza A(H1N1)pdm09 in the second year of its circulation than in the pandemic year [23].…”
Section: Tablementioning
confidence: 99%
“…The global influenza A/H1N1 (H1N1) pandemic in 2009 was associated with high morbidity and mortality [1,2]. Healthcare workers (HCWs) are identified as being at high-risk of being infected with influenza A/H1N1 during such epidemics [3,4].…”
Section: Introductionmentioning
confidence: 99%